Perceptions of Fellowship Trainees in Public and Private Tertiary Care Hospitals of Karachi - Sadaf zia (Journal of Islamabad Medical and Dental College, 2020)
Background: The issues pertaining to postgraduate medical education have been debated for long but there has been little contribution to this literature from developing countries. Therefore, a need to make an accurate assessment regarding current status of postgraduate training in Pakistan was felt and feedback from residents is the cornerstone of such an assessment. The objective of our study was to document perceptions of FCPS trainees of medical and surgical disciplines in private and public tertiary care hospitals of Karachi, Pakistan. Material and Methods: This was a cross sectional survey of the medical and surgical FCPS trainees in three hospitals (1 public and 2 private) of Karachi Pakistan, conducted over a period of two months (1st November 2018 to 31st December 2018). A total of 325 participants selected by convenient sampling technique were included in the study. Data was collected through structured self-developed questionnaire and analyzed by SPSS version 16.0. Results: The percentage of postgraduate trainees in private hospitals working for more than 80hours/week is higher than those working in public sector hospitals (59.4% versus 42.4%). Topic presentation and Academic meetings (Conferences, Workshops and CMEs) were the most preferred teaching strategies in Postgraduate training (77.4% and 77.5%). About 62.7% of the residents believed that their program was in line with CPSP guidelines. Public sector hospitals were better in terms of medical benefits giving partial cover (62.8%) than private sector (P-value <0.001). Majority of trainees at private sector hospitals seemed satisfied with their working environment than at public hospital (77.5% versus 12.5%) (P-value <0.001). Trainees perceived that the security arrangements at both public and private hospitals were not adequate, but in case of emergency private hospitals seemed to have better security response as compared to public hospitals (89% versus 23%) with a significant difference of <0.001. Conclusion(s): Perception of most of the postgraduate trainees is that they are being adequately trained for the challenges of an independent physician or surgeon